Financial Sector Policy Note : Financing Small and Medium-Sized Businesses in Burkina Faso - Soubeiga, Sidiki (World Bank, Washington, DC, 2014)
As in other Sub-Saharan African countries, small and medium-sized enterprises (SMEs) represent the vast majority of firms operating in the private sector in Burkina Faso. Private sector-led growth is a major element of Burkina Faso's poverty reduction strategy, la strategie de croissance accelere et le developpement durable. Unfortunately, many characteristics of Burkina Faso's business environment, and of businesses themselves, make private sector-led growth a challenge. This financial sector policy note focuses on the market for credit and closely related financial services, how private banks are providing these services to SMEs, and recommendations that address problems they are having. This requires understanding the behavior of banks with respect to SME lending, particularly investment lending and related financial products like leasing, guarantees, microcredit, and subsidized credit funds. This policy note consists of a study and survey of commercial banks and two non-bank financial institutions (NBFIs) (Burkina Bail and Societe Financiere de Garantie Interbancaire du Burkina (SOFIGIB) focusing on lending to SMEs. It focuses on the supply side of the market. The survey and accompanying interviews took place during the summer of 2013. Twelve private banks and five NBFIs were asked to participate in the study and survey. The study references two additional surveys focused on SMEs: (1) the 2009 World Bank enterprise survey, and (2) the 2012 survey of SMEs commissioned by the ministry of industry, trade, and artisans. The study consists of observations and analysis of survey data to provide input to policies for encouraging lending to SMEs and increasing the provision of other financial services. This report is structured as follows: executive summary; purpose and structure of policy note; macroeconomic context and the banking sector section provides a description of the situation in which Burkina Faso finds itself. Demand for SME finance section presents recent studies focused on the demand for credit by SMEs. Supply of SME finance section presents the results of the survey organized around the keys issues facing the provision of credit to SMEs. Enabling environment for financing SMEs section discusses salient characteristics of the business, legal, and regulatory environment that effect SME finance; recommendations; and conclusions.